The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/1536383x.2019.1686627
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterials based on plant biopolymers as radionuclides sorbent

Abstract: The technogenic human activities associated with the operation of nuclear power facilities lead to the contamination of natural water bodies and soils with radioactive substances, including heavy radionuclides, such as uranium and thorium. Purification of natural water bodies is a pressing environmental issue. A study of the adsorption capacity for heavy U238 and Th232 radionuclides by the samples of new carbon nanomaterials was conducted. Nanocarbon materials was synthesized based on vegetal polymers, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As well as these carbon nanomaterials, a considerable number of new ones are constantly being discovered or synthesized. The following varieties of nanocarbon are also frequently used: (i) carbon nanodots, offering various applications such as electronics and optoelectronics, which should be noted [8]; (ii) mesoporous carbon nanomaterials, with applications in biomedical Materials 2021, 14, 5304 2 of 11 engineering such as drug delivery [9] or chemical adsorbents [10]; and (iii) the group of lignin-based, starch-based, and bark-based carbon nanomaterials, classified as so-called graphene nanoplatelets, with proven high adsorption properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…As well as these carbon nanomaterials, a considerable number of new ones are constantly being discovered or synthesized. The following varieties of nanocarbon are also frequently used: (i) carbon nanodots, offering various applications such as electronics and optoelectronics, which should be noted [8]; (ii) mesoporous carbon nanomaterials, with applications in biomedical Materials 2021, 14, 5304 2 of 11 engineering such as drug delivery [9] or chemical adsorbents [10]; and (iii) the group of lignin-based, starch-based, and bark-based carbon nanomaterials, classified as so-called graphene nanoplatelets, with proven high adsorption properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbons are synthesized from various raw materials as precursors, lignocellulosic being one of the most used precursors, which has many advantages such as the simplicity of the synthesis process, the high reactivity, the low costs, the negative impact to the environment, and the availability of precursors. [3,4] Among these precursors, it can be mentioned coconut shell, [5,6] Tamarind wood, [7] Paulownia wood, [8] lignin, [9] cotton stalks, [10,11] Spartina Alterniflora, [12] Fox nut, [13] wild chestnut, [14] pumpkin seed shell, [15] tobacco stem, [16] black wattle bark waste, [17] Oleaster cores. [18] In the present study, the ability of Silver berry seeds to serve as a low-cost material for the synthesis of Granular Activated Carbon (GAC) was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that, in terms of their morphometric parameters, the obtained 2D graphene structures belong to FLG [7]. To date, it has been shown that the obtained FLG is promising in polymer materials science [9], as a basis for radionuclides sorbent [10]. The ability to obtain FLG in product volume sufficient for real application and the shown promise of their use in a wide range of practical applications determined the choice as an object of this research FLG synthesized using the SHS process.…”
Section: Introductionmentioning
confidence: 94%